Answer:
(-4x - 2)(-5x) + (-4x - 2)(3)
Step-by-step explanation:
Your polynomial is
(-4x - 2)(-5x + 3)
The distributive property states that
a(b + c) = ab + ac
Let a = -4x - 2. Then
(-4x - 2)(-5x + 3) = a(5x + 3) = a(-5x) + a(3)
Substitute the value of a.
a(-5x) + a(3) = (-4x - 2)(-5x) + (-4x - 2)(3)
You have just distributed the first binomial (-4x - 2) among the terms of the second binomial.
Answer:
541
Step-by-step explanation:
6492 / 12 = 541 pages
Answer:
y=2x-1
Step-by-step explanation:
Remeber to put no spaces on the test
and it is this answer bc he owes one dollar evryday and owing is negative
B
Because 2 sqrt5 is = to sqrt 20.
4^2=16, 6^2=36